The Crowding out Effect on the Labor Market in Romania - Mihaela Hrisanta DOBRE (Theoretical and Applied Economics, 2011)

(untitled)
Discrimination expresses any distinction, exclusion, restriction, preference or different treatment that disadvantages a person or group, in comparison with others in similar situations. The crowding out effect was first formulated by Bergmann (1974) and explains that an individual can obtain lower returns if he belongs to a branch dominated by the members of another group. The difference in pay between women and men is also reinforced by the segregation in the labor market, which may explain the crowding out effect.    In this article we analyzed the level of segregation in the Romanian labor market starting from the workers professional status and their distribution by branch from 2003 to 2008. Crowding out effect was analyzed based on the gain function of the two groups (women and men).